Implementation of a Digital e-Module in Marriage Guidance at KUA Rengasdengklok District - Qonita Nurshabrina; Moh Ali; Nasehudin Nasehudin; Hasri Nur Azizah (Yayasan Rahmat Islamiyah, 2026)
This study aims to analyze the implementation of a digital e-module in Marriage Guidance (Bimbingan Perkawinan) as an innovative learning medium and to examine its impact on participants’ understanding, motivation, and internalization of sakinah family values. This research employed a descriptive qualitative approach supported by quantitative data. Data were collected through observation, questionnaires distributed via Google Forms, and documentation, and were analyzed descriptively using percentage techniques. The findings indicate that the digital e-module was effectively implemented as a flexible and interactive learning medium in a flipbook format accessible through QR codes. Participants demonstrated positive learning responses, reflected in ease of access, improved understanding of sakinah family concepts, and a strong intention to apply these values in their future marital life. The e-module also promotes independent and reflective learning, enabling deeper internalization of Islamic family values.